Identification of Drosophila melanogaster as a model organism in COPD research - Zhang, Yuan; Kou, Jing; Zhang, Yuxuan; Huang, Haiyi; Yang, Yang; Liu, Chengshuang; Lu, Ting; Zhao, Xiaoxuan; Liu, Yongqi; He, Jianzheng (Frontiers in Immunology, 2026)
Chronic obstructive pulmonary disease (COPD) is a progressive respiratory condition characterized by increasing mortality and morbidity. Current animal models have certain limitations in elucidating the pathophysiology and underlying mechanisms of COPD, which hinder effective treatments. There is an urgent need to identify an informative model that can dissect the COPD mechanisms and screen therapeutic drugs. The Drosophila melanogaster is regarded as an ideal in vivo model for studying COPD due to its ability to present representative pathological hallmarks within a short time frame, its visualized tracheal morphology, and well-established genetic tools. In this study, we explore the feasibility of using Drosophila as a novel invertebrate model for investigating COPD. We summarize the conserved features between flies and mammals in response to airway inflammation, including airway structures, pathophysiological changes, immune responses, molecular mechanisms, and modeling approaches. Additionally, we outline potential translational applications, including high-throughput identification, drug discovery, and a prioritized preclinical platform. We also propose integrating insights from Drosophila with mammalian models and clinical COPD endotypes.